Determinan Pendapatan Peternak Ayam Pedaging di Kecamatan Marga Kabupaten Tabanan - I.M.F. Irawan; I. N. G. Marta; N. W. Murthi; I. K. Djayastra (Institut Agama Islam Sunan Giri Ponorogo, 2024)
The demand for animal food from livestock (meat, eggs and milk) tends to increase over time in line with population growth, income, nutritional awareness, and improvements in education levels. Marga District, Tabanan Regency as the top three broiler chicken populations that are very close to the city center, still has great potential to be developed as a broiler chicken production site because there is still a lot of land and labor in rural areas that can be empowered. The increase and decrease in the broiler chicken population is certainly indirectly in line with the income of chicken farmers in Tabanan Regency, because it can be interpreted that the chicken population increases, income can increase and likewise if the chicken population decreases, then the income of farmers can also decrease. The purpose of this study was to determine the effect of labor, capital and length of business on broiler chicken production simultaneously and partially. This study uses quantitative research methods and statistical analysis, especially numerical analysis and statistical analysis with the aim of confirming the previously established hypothesis. This study used a sample of 63 farmers through data collection through interviews and questionnaires, with multiple linear regression methods, partial tests and simultaneous F tests. Based on the results of the SPSS calculation, the results obtained are that the variables of capital, use of labor and length of business simultaneously/together have a significant effect on the income of broiler chicken farmers. Capital, labor have a positive and significant effect partially on the income of chicken farmers, while the length of business has a positive but not significant effect on chicken Farmers